2007
DOI: 10.1021/nl072003g
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Growth of Highly Luminescent CdSe/CdS Nanoheterostructures with Rod and Tetrapod Morphologies

Abstract: We have demonstrated that seeded growth of nanocrystals offers a convenient way to design nanoheterostructures with complex shapes and morphologies by changing the crystalline structure of the seed. By using CdSe nanocrystals with wurtzite and zinc blende structure as seeds for growth of CdS nanorods, we synthesized CdSe/CdS heterostructures nanorods and nano-tetrapods, respectively. Both of these structures showed excellent luminescent properties, combining high photoluminescence efficiency (~80% and ~50% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
1,008
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(1,049 citation statements)
references
References 34 publications
32
1,008
1
4
Order By: Relevance
“…Radiative recombination typically takes place at the CdSe core at the centre of four rod-like CdS arms, and extensive leakage of the CdSe electron wavefunction into the CdS shell results in a dramatic redshift in its optical spectra relative to the original CdSe NC seed. [ 9 ] The ensuing reduced spatial overlap between the CdSe electron and hole wavefunctions is expected to yield suppressed Auger recombination rates, as was previously observed in a related system of CdSe seeded CdS nanorods exhibiting relatively long biexciton lifetimes of ∼ 300 ps. [ 10 ] While it has been suggested that CdSe seeded CdS nanotetrapods hold promise as good NC-based optical gain materials, [ 9 , 11 ] however, ASE from such structures has to the best of our knowledge not yet been demonstrated.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 65%
See 2 more Smart Citations
“…Radiative recombination typically takes place at the CdSe core at the centre of four rod-like CdS arms, and extensive leakage of the CdSe electron wavefunction into the CdS shell results in a dramatic redshift in its optical spectra relative to the original CdSe NC seed. [ 9 ] The ensuing reduced spatial overlap between the CdSe electron and hole wavefunctions is expected to yield suppressed Auger recombination rates, as was previously observed in a related system of CdSe seeded CdS nanorods exhibiting relatively long biexciton lifetimes of ∼ 300 ps. [ 10 ] While it has been suggested that CdSe seeded CdS nanotetrapods hold promise as good NC-based optical gain materials, [ 9 , 11 ] however, ASE from such structures has to the best of our knowledge not yet been demonstrated.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 65%
“…Atomic Force Microscope (AFM) measurements on the resulting tetrapodsilica composite fi lm, as exemplifi ed in Figure 1 (b), yielded a smooth morphology with a typical surface roughness (RMS) of about ∼ 7.5 nm, over a 1 μ m 2 scan area, suggesting a uniform incorporation of tetrapods into the sol-gel derived silica matrix. Absorbance measurements, profi lometry analysis of the fi lm thickness and the molar absorptivity of CdSe seeded CdS tetrapods determined via a previously reported method [ 9 ] provided an estimate of the volume fraction of tetrapods in the silica fi lm, which was about ∼ 6-10% for all the fi lms presented in this work. It is important, however, to note that the volume fraction with respect to the CdSe core is less than 1% given the dominant contribution of CdS to the overall volume of the CdSe seeded CdS tetrapod structure.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 88%
See 1 more Smart Citation
“…In 2003 a dot‐in‐rod architecture of a CdSe dot within a CdS rod was introduced,82 and later a seeded growth synthesis for this interesting system was reported 83, 84. This CdSe/CdS dot‐in‐rod heterostructure system has a mixed dimensionality as it integrates a 0D confined seed within a 1D confined system.…”
Section: Quantum Confinement Heterostructures and Shape Effects In mentioning
confidence: 99%
“…We can conclude that, by pumping well above the CdS band-edge, hot carrier trapping in the shell (at a rate τ tr ) may still limit the number of excitons reaching the lowest energy state in the CdSe core. Further support for this notion stems from PL excitation spectroscopy in CdSe/CdS Qdot-in-rods, showing a reduced PL QE when pumping the material above the CdS absorption edge, [ 20 ] and from transient absorption measurements on CdSe Qdots, in which fast (ps-timescale) hot exciton trapping has also been observed. [ 21 ] For such bare nanocrystals it lead to strongly suppressed gain when pumping them at 400 nm.…”
Section: Op233mentioning
confidence: 99%